A agência na formação de uma professora de Língua Estrangeira Espanhola em contexto pré-serviço - Fonseca, Lucilene Santos Silva (2015)
The overall objective of this research is to investigate the agency of an undergraduate student of the Faculty of Language and Arts in Spanish language, along her work in the discipline Practice of Foreign Language Teaching (FL), permeated by the actions of the teacherresearcher in a university located in a city of the metropolitan area of São Paulo. We have perceived that many of these students, after completing graduation, start teaching classes in elementary and high schools without the practical experience of teaching a foreign language (LE). This problem motivated the following specific objectives with this focus: (1) identify language features that enable us to understand the agency of the participant; (2) identify how the proposals of the discipline enable the development of the agency of the participant; (3) analyze the type of agency revealed in the development of the participant. The theoretical and methodological choice in constructing contexts of comprehension, reflection and transformation, with respect to the teaching and learning of languages and the role of language in these contexts is endorsed by the Critical Collaboration Research (MAGALHÃES, 2010). This theoretical framework is based on the Theory of Socio- Historical-Cultural Activity (VYGOTSKI, 1934/1998, 1930/1999; LEONTIEV, 1978; ENGESTRÖM, 2001), focusing on the concepts of teaching and learning and development, mediation and Zone of Proximal Development (ZPD) as a socio-cultural-historical space of coming to be, in which language organizes a collaborative-critical relationship between the participants. Data has been collected aiming to recover and understand the agency of the work done by the undergraduate student during the discipline Foreign Language Teaching Practice. First we selected thrirteen (13) texts done by the undergraduate student through her activities as a teacher in pre-service. This work is justified for collaborating with discussions about Faculty undergraduate courses with degree in Foreign Languages (FL) and the agency's role in the development of the discipline Teaching Practice of FL. This work integrates CNPq, Contradiction and Collaboration Research, led by PHD. Professor Maria Cecilia Magalhães Camargo of the da PUC-SP University which aims to investigate ways of questioning, presenting, countering arguments that constitute activities of school context, with emphasis on teacher training, such as reproductive and/or creative productions of meaning for proposing a research framework and organization of these activities in more creative perspectives. Therefore, this research can contribute to benefit educational entities that seek to improve the pre-service teacher training and students of Language and Arts and Literature